PROTOTYPE PEMBELAJARAN LIFT TIGA LANTAI BERBASIS ARDUINO - Ghoni Musyahar; Miftakhul Huda (Universitas Muhammadiyah Pekajangan Pekalongan, 2017)
In the globalization era, There are many multistoried buildings with different heights scale. This is also due to facilitate community activities at the same place, so we need some elevator control system design that serves as a means of transportation that is connecting vertically between floors of a building. Simulation tool consists of a series of DC motor controller which is governed by the system microcontroller with input push button switchs . In the circuit of DC motor controllers, direction of rotation and speed set by the driver motor. For microcontroller as controller, selected from types Arduino Uno R3 with the programming C language. In the process control, elevators will move vertically either move up or move down in accordance input selector button.